The Role of Local Wisdom in Addressing the Character Education Crisis in the Age of Modernization - Aylatus Sya Khiya; Erlanda Erlanda; Ismu Anggun Surya Maulidiyah; Moh Faizin (al-Afkar, Journal For Islamic Studies, 2026)
The rapid progression of modernization and globalization has triggered a fundamental reorientation of values among younger generations, manifesting in the erosion of students' character formation, while prevailing educational practices are widely regarded as overly prescriptive and inadequately attuned to the socio-cultural realities students inhabit. This study pursues three primary objectives: (1) to examine the forms and dimensions of the character education crisis amid modernization, (2) to investigate the strategic function of local wisdom in responding to this crisis, and (3) to delineate how local wisdom values may be embedded within instructional processes as a mechanism for cultivating students' character. A qualitative methodology grounded in library research was applied, involving systematic analysis of pertinent scholarly literature. Three principal findings emerged from this inquiry: (1) local wisdom is established as a contextually grounded and value-laden alternative within character education, (2) contextual learning approaches demonstrate greater efficacy in facilitating value internalization relative to conventional, norm-driven instruction, (3) the incorporation of local cultural values into formal educational structures is put forward as a strategically informed response to contemporary character deterioration. It is therefore argued that local wisdom should not be relegated to a peripheral curricular role, but rather positioned as a foundational framework, systematically embedded through institutionalized school culture practices and the enrichment of learning experiences beyond the formal classroom setting.